ENTREPRENEURIAL BRICOLAGE AND IMPROVING THE CAPABILITY OF WOMEN WEAVING ENTREPRENEURS - Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi; Puah, Chin-Hong (Jurnal Aplikasi Manajemen, 2022)
The COVID-19 pandemic has put a lot of pressure on the women-run weaving industry, one of which is a decline in demand and the loss of opportunities for women to support the economic life of their families amid global efforts to improve gender equality and women's welfare. This research is expected to solve the inequality problem, especially for women, supporting economic growth and achieving prosperity. Efforts to empower women are expected to increase innovation and productivity amidst scarce resources. The research objective is to analyze the role of women in achieving business productivity and subjective welfare through strengthening the position of bricolage. In addition, material flexibility in managing resource constraints and highlighting the development of a company-specific social resource environment by exploring bricolage from an institutional aspect. The sample in this study were 112 women who own the weaving handicraft business in Bali Province, which were obtained using a saturated sampling method. Research data collection using observation and interview. Data were analyzed using a structural equation model, namely Partial Least Square. The study results reveal a strong influence of bricolage for women's empowerment on improving business performance. Other dimensions that affect subjective welfare are empowerment, entrepreneurial orientation, bricolage, business networks, and business performance. Weaving business players strive for innovation as the primary key factor in surviving in a dynamic environment and changing technology. Further research can use the government's role and technology implementation variables to improve weaving artisans' welfare.